Mobile game for the elderly: Bundled Bingo Game - Chin, Yi Jia; Lim, Woan Ning *; Lee, Chien Sing * (2017)
The aim of this project is to develop a customized Bingo game based on the user interface guidelines that suit the elderly users. This project targeted to improve the cognitive ability of the elderly with the specifically designed gaming features. In this research, qualitative data will be used to analyze the confidence and acceptance level of the elderly on the mobile digital games, as well as to understand how the elderly interacts with current technologies (mobile devices) and the benefit they can gain from the mobile games. User testing, survey, and result analysis have been done with a group of elderly members from D’Happy club in Petaling Jaya, Malaysia. The results of this project contribute to the development of an elderly friendly mobile game to motivate the elderly’s engagement in mobile gaming, with the will that it could help to delay and decrease the risk of the elderly in developing the Alzheimer’s disease.